Информация стратегического управленческого учета: формирование и использование в системе управления предприятием - Ершова, Наталья Юрьевна; Ткаченко, Марина Алексеевна; Гаркуша, Виктория Александровна (Premier Publishing s.r.o.,Vienna, 2019)
Статья посвящена вопросам формирования и использование информации стратегического управленческого учета в системе управления предприятием. Предложены принципы формирования информации стратегического управленческого учета, обоснован и предложен методический подход к оценке качества информации. Раскрыта практическая значимость полученных результатов.

In the article, the formation and use of information of strategic management accounting in the enterprise management system is investigated. Principles of formation of information strategic management accounting proposed. A methodical approach to assessing the quality of information formation has been developed. The practical significance of the results are determined.
Information strategic management accounting: the formation and use of enterprise management system
Keywords: критерии качества информации; пользователи информации; управленческие решения; information quality criteria; information users; principles of formation; strategic management accounting; enterprise management